Ferulic Acid Protects Hyperglycemia-Induced Kidney Damage by Regulating Oxidative Insult, Inflammation and Autophagy - Chowdhury, Sayantani; Ghosh, Sumit; Das, Abhishek Kumar; Sil, Parames C. (Frontiers in Pharmacology, 2019)
Oxidative insult, inflammation, apoptosis and autophagy play a pivotal role in the etiology of diabetic nephropathy, a global health concern. Ferulic acid, a phytochemical, is reported to protect against varied diseased conditions. However, the ameliorative role and mechanisms of ferulic acid in averting STZ-mediated nephrotoxicity largely remains unknown. For in vivo study, a single intraperitoneal injection of streptozotocin (50 mg kg−1 body wt.) was administered in experimental rats to induce diabetes. The diabetic rats exhibited a rise in blood glucose level as well as kidney to body weight ratio, a decrease in serum insulin level, severe kidney tissue damage and dysfunction. Elevation of intracellular ROS level, altered mitochondrial membrane potential and cellular redox balance impairment shown the participation of oxidative stress in hyperglycemia-triggered renal injury. Treatment with ferulic acid (50 mg kg−1 body wt., orally for eight weeks), post-diabetic induction, could markedly ameliorate kidney injury, renal cell apoptosis, inflammation and defective autophagy in the kidneys. The underlying mechanism for such protection involved the modulation of AGEs, MAPKs (p38, JNK and ERK 1/2), NF-κB mediated inflammatory pathways, mitochondria-dependent and -independent apoptosis as well as autophagy induction. In cultured NRK-52E cells, ferulic acid (at an optimum dose of 75 µM) could counter excessive ROS generation, induce autophagy and inhibit apoptotic death of cells under high glucose environment. Blockade of autophagy could significantly eradicate the protective effect of ferulic acid in high glucose-mediated cell death. Together, the study confirmed that ferulic acid, exhibiting hypoglycemic, antioxidant, anti-inflammatory, anti-apoptotic activities and role in autophagy, could circumvent oxidative stress-mediated renal cell damage.